(untitled) (Computer systems and information technologies, 2024)
The article presents the main sources of renewable energy (RES), including solar, wind, hydropower, as well as biomass energy and geothermal energy. The importance of these sources lies in reducing the dependence on fossil fuels and reducing greenhouse gas emissions. An analysis of RES facilities and their implementation technology was carried out. The current state and prospects for the development of renewable energy sources in Ukraine and around the world are analyzed. In 2018, Ukraine joined IRENA to develop RES. According to the agency, by the end of 2023, renewable energy sources accounted for 43% of the installed capacity. The total number of renewable energy facilities is increasing annually, but renewable energy sources account for half of the total capacity. 2023 saw the largest increase in renewable energy capacity to date (with the addition of 473 GW of renewable energy), a 13.9% increase in renewable energy reserves. Renewable energy accounts for a record 86% of the increase in world electricity, largely due to the significant growth of solar and wind power. In addition, the article emphasizes the importance of the reliability and efficiency of installations using renewable energy sources. The main methods for detecting damage in renewable energy systems are described. Detection methods based on acoustic emission, ultrasound, vibration, thermography, machine vision, and strain measurement are used most frequently to detect RES damage. The development of renewable energy sources stimulates economic growth and creates new jobs in the production, installation, maintenance, and management of energy installations. Investments in green energy contribute to the development of technologies, increasing competitiveness, and the creation of innovative sectors of the economy.